End-of-winter snow water equivalent in Jarvis Creek watershed, Interior Alaska, 2011-2016 - Anna Liljedahl (Arctic Data Center, 2017)
The overall project assessed the linkages and controls of a subarctic glacier-permafrost hydrological system from a watershed-scale perspective using field measurements, remote sensing and numerical modeling. Jarvis Creek (634km²), which feeds the Delta and Tanana River in Interior Alaska, was studied as a proxy of the observed mountain glacier melting and permafrost degradation that has been documented across the Arctic region in recent decades. The specific objectives were to 1) assess the hydrologic fluxes (including streamflow source components), stores, pathways and the role of glacier wastage on watershed hydrology, through hydrologic and geochemical field measurements as well as numerical and statistical modeling; 2) quantify the effect of glaciers and permafrost on recent historical (1960-present) hydrologic fluxes and storage by combining remote sensing, field measurements of glacier mass balance, and hydrology with a heat- and mass transfer model, and 3) project the future hydrologic regime using custom-derived downscaled climate projections. The purpose of this dataset was to quantify the variability in end-of-winter snow depth, snow density and snow water equivalent (SWE) across a range of vegetation types (forest to dwarf-shrub alpine tundra) in the lowland and lower mountain areas of Jarvis Creek watershed during a six year time period. The measurements informed assessments of watershed hydrology.